AN EXPLORATION OF PARTNERSHIP WORKING BETWEEN THE YOUTH JUSTICE SERVICE AND THE MULTI-AGENCY SAFEGUARDING HUB & FIRST RESPONSE TEAM IN RELATION TO SAFEGUARDING REFERRALS REGARDING YOUNG PEOPLE SUPERVISED BY THE YOUTH JUSTICE SERVICE - Anna Perumall (Society Register, 2017)
The drive behind this paper is to explore the quality of the partnership working between the Youth Justice Service and the Multi – Agency Safeguarding Hub & First Response Team in one of the London Boroughs on the basis of 6 selected cases which were known to both services. The study begins with an explanation of the rationale for the research and an introduction to both services and their roles. Subsequently, I review the literature, publications and relevant government policies linked to this topic. Successively, I concentrate on methodology employed in the study and any ethical issues arising as well as the theory underpinning the research. Next part presents the findings and offers an analysis. Finally, the paper outlines the conclusions of this piece of work with a brief summary of recommendations for both services in order to enhance the understanding of their roles as well as how to work better together in order to achieve improved outcomes for young people.